Perspectives on the Practicability of Li‐Rich NMC Layered Oxide Cathodes - Li, Biao; Zhang, Kun; Yang, Yali; Zuo, Yuxuan; Li, Xiang; Xia, Dingguo (Advanced materials (Weinheim), 2024)
Li‐rich NMCs layered oxides, with the general formula of Li[LixNiyMnzCo1−x−y−z]O2, are known for their exceptionally high capacities but remain yet to be practicalized in the real world. They have attracted enormous research attention due to their complex structure and intriguing redox mechanisms, with a particular focus on anionic redox over the past decade. While fundamental understandings are fruitful, the practical considerations are emphasized here by providing perspectives on how Li‐rich NMCs are limited by practical roadblocks and guidelines on how to cope with these limitations. It is also demonstrated that, via a techno‐economic analysis, Li‐rich NMCs have material cost ($/kg) highly dependent on the lithium price, but still preserve the dominance of lower pack cost ($/kWh) than other cathode candidates principally owing to their larger material energy densities. In addition to their pure application in electric‐vehicle batteries, using them as “electrode additive” or “sacrificial agent” can further multiply their practicalities in assortment of scenarios, which is further discussed. This perspective presents how the practicability of Li‐rich NMCs is limited by issues like tap density, electrolytes, gas generation, voltage hysteresis, and decay. A techno‐economic analysis is also provided to show that Li‐rich NMCs have material cost highly dependent on lithium price, but still preserve the dominance of lower pack cost than other cathode candidates.